Influence of the sealer and a plug in coronal leakage after post space preparation - Holland, Roberto [UNESP]; Murata, Sueli Satomi [UNESP]; Silva, Monica Nunes Da; Dezan Junior, Eloi [UNESP]; Souza, Valdir de [UNESP]; Bernabé, Pedro Felício Estrada [UNESP] (Faculdade De Odontologia De Bauru - USP, 2004)
The subject of this paper was to conduct an in vitro study of the coronal leakage after root canal filling and post space preparation. One hundred single-rooted human teeth had their crowns removed and the canals prepared and filled by the lateral condensation technique with gutta-percha points and the sealers CRCS and Endofill (a Grossman cement). After post space preparation, the remainder of the filling was protected or not with 1mm of a plug of the following materials: Coltosol, Super Bonder (cyanoacrylate-ester), CRCS and Endofill. After 24 hours in saline, the specimens were immersed in a 2% methylene blue solution in a vacuum environment for 24 hours. The teeth were then sectioned longitudinally, leakage was evaluated linearly and the obtained data were submitted to the Kruskal-Wallis test. The results with the two sealers studied were similar between themselves and worse (p<0.01) than the groups with a protector plug. The statistical analysis ordered the experimental groups from the best to the worst in the following way: a - Endofill-Super Bonder, CRCS-Super Bonder, CRCS-CRCS; b - Endofill-Endofill; c - Endofill-Coltosol, CRCS-Coltosol; d - Endofill, CRCS.

O objetivo deste trabalho foi avaliar in vitro a infiltração marginal coronária após obturação de canal e preparo para pino, empregando-se ou não um plug protetor. Cem dentes humanos unirradiculares extraídos tiveram suas coroas removidas, e os canais preparados biomecanicamente e obturados pela técnica da condensação lateral com cones de guta-percha e os cimentos CRCS e Endofill. Após preparo para pino, os remanescentes das obturações foram ou não protegidos por 1 mm de um plug dos seguintes materiais: Coltosol, Super Bonder, CRCS e Endofill. Após permanecerem 24 horas em soro fisiológico, os espécimes foram imersos em solução de azul de metileno a 2%, em ambiente com vácuo, por 24 horas. Os dentes foram então seccionados longitudinalmente, as infiltrações marginais mensuradas linearmente, e os dados obtidos submetidos à análise de variância e teste de Kruskal-Wallis. Os resultados com os 2 cimentos estudados foram semelhantes entre si e piores (ñ<0,01) do que os grupos com plugs protetores. A análise estatística ordenou os grupos experimentais do melhor para o pior da seguinte maneira: a- Endofill-Super Bonder, CRCS-Super Bonder, CRCS-CRCS; b- Endofill-Endofill; c- Endofill-Coltosol, CRCS-Coltosol; d- Endofill, CRCS.
Influência do cimento obturador e de um plug na infiltração coronária após preparo para pino
Keywords: Coronary leakage; Endofill; CRCS; Plug; Post space preparation; Infiltração coronária; Endofill; CRCS; Plug; Preparo para pino